The Role of the Mitra Sejahtera Raya Indonesia Sharia Savings, Loans and Financing Cooperative in the Development of Micro, Small and Medium Enterprises (MSMEs) in Pakuhaji District, Tangerang Regency. - Kusnadi, Kusnadi; Purwanto, Agus (AGUSPATI Research Institute, 2025)
Mitra Sejahtera Raya Indonesia Sharia Savings and Loans Cooperative is a sharia financial institution active in community activities and provides savings and loan services and financing in accordance with sharia principles, primarily through murabahah financing. Despite its profitable characteristics and low risk, communities in Tangerang Regency, particularly Pakuhaji District, still face difficulties in developing their businesses due to the difficulty in obtaining capital. This study used a field method with a qualitative descriptive approach, involving interviews with seven informants and direct observation. The results showed that KSPPS plays a role in empowering MSMEs by providing appropriate business capital, improving human resource quality, and conducting training. The level of member welfare also increased after receiving financing. In conclusion, Mitra Sejahtera Raya Indonesia Sharia Savings and Loans Cooperative has contributed positively to empowering MSMEs in Tangerang Regency.